Approaches to Sedation in Pediatric Neuroimaging: What the Radiologist Should Know - Fawole, Chiagozie; Webber, Audra (Journal of Pediatric Neurology, 2018)
Magnetic resonance imaging (MRI) is a safe and effective imaging technique that avoids exposure to ionizing radiation. The volume of pediatric MRI studies is increasing and with it the number of studies performed with sedation or anesthesia. When sedation or anesthesia are necessary for image acquisition there is an additional layer of complexity and the risks to the patient versus the benefits of imaging must be weighed. The purpose of this review is to describe sedation and anesthesia as it is utilized for MRI. Common techniques and inherent risks are discussed, as are recent controversies in and alternatives to sedation or anesthesia. The importance of collaboration and communication among providers is emphasized along with patient safety.
Keywords: sedation; anesthesia; pediatric; neuroimaging; magnetic resonance imaging